Uncovering the re-distribution mechanism of Ni in a de-alloyed Ni-Cr alloy in molten fluorinated salts - Sean H. Mills; Ho Lun Chan; Nathan Bieberdorf; Elena Romanovskaia; Valentin Romanovski; Minh H. Tran; Laurent Capolungo; Mark Asta; John R. Scully; Andrew M. Minor; Peter Hosemann (npj Materials Degradation)
Abstract A mechanism of Ni redeposition during dealloying corrosion of Ni-Cr is investigated. A model Ni20Cr (wt%) metal alloy was exposed to molten LiF-NaF-KF eutectic (FLiNaK) at 600 °C and at an applied potential of +2.1 VK+/K, above the critical potential for onset of dealloying. Upon extended exposure times (up to 12 h), prominent salt-filled corrosion channels emerge along grain boundaries. A unique grain boundary corrosion mechanism, with respect to the exposed faces of the grains, a central focus of this investigation, is intrinsically connected to the formation of high purity Ni-rich de-alloyed regions within the salt-filled channel. We implement microscale techniques such as energy dispersive spectroscopy (EDS) and electron backscatter diffraction (EBSD) to uncover morphological and compositional variations in relevance to the formation of bicontinuous porosity from corrosion dealloying. To rationalize our findings, a phase-field model is developed and discovers a mechanism in which dissolved Ni from one grain can be redeposited on an adjacent grain at a given difference in interfacial energies. The interaction of chemical and structural factors at the grain boundaries plays a central role in elucidating the dynamics of this phenomenon and its implications towards corrosion.